Signaling Cascade of Diacylglycerol Kinase β in the Pituitary Intermediate Lobe: Dopamine D2 Receptor/Phospholipase Cβ4/Diacylglycerol Kinase β/Protein Kinase Cα - Hozumi, Yasukazu (Histochemical Society, 2010)
The pituitary gland dynamically changes its hormone output under various pathophysiological conditions. One of the pathways implicated in the regulatory mechanism of this gland is a dopaminergic system that operates the phosphoinositide (PI) cycle to transmit downstream signal through second messengers. We have previously shown that diacylglycerol kinase β (DGKβ) is coexpressed with dopamine D1 and D2 receptors in medium spiny neurons of the striatum, suggesting a plausible implication of DGKβ in dopaminergic transmission. However, it remains elusive whether DGKβ is involved in the dopaminergic system in the pituitary gland. The aim of this study is to investigate the expression and localization of DGK in the pituitary gland, together with the molecular components involved in the PI signaling cascade, including dopamine receptors, phospholipase C (PLC), and a major downstream molecule, protein kinase C (PKC). Here we show that DGKβ and the dopamine D2 receptor are coexpressed in the intermediate lobe and localize to the plasma membrane side by side. In addition, we reveal that PLCβ4 and PKCα are the subtypes expressed in the intermediate lobe among those families. These findings will substantiate and further extend our understanding of the molecular-anatomical pathway of PI signaling and the functional roles of DGK in the pituitary intermediate lobe. (J Histochem Cytochem 58:119–129, 2010)